1995
DOI: 10.1097/00000539-199509000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Propofol Administration Techniques for Sedation During Monitored Anesthesia Care

Abstract: Sixty-three outpatients undergoing breast biopsy procedures with local anesthesia were randomly assigned to receive propofol by intermittent bolus injections (n = 21), a conventional syringe infusion pump (n = 21), or a target-controlled infusion (TCI) device (n = 21) for intraoperative sedation. In the first two groups, an initial intravenous (IV) bolus of propofol (0.3 mg/kg) was administered and an attempt was made to maintain the sedation level at an Observer's Assessment of Alertness/Sedation (OAA/S) scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 20 publications
1
29
0
3
Order By: Relevance
“…Previous studies evaluating different techniques of propofol administration during monitored anesthesia care demonstrated that, although the overall quality of sedation, operating conditions and clinical recovery profiles were similar with different administration techniques, the anesthesiologist had to intervene more frequently with the intermittent bolus injection technique than either conventional syringe infusion or target-controlled infusion techniques. 17 While it has been reported in large multicentre trials, that target-controlled infusion systems are easily learned and well accepted by anesthesiologists in their daily practice) 8 A wide variety of objective clinical scoring systems has been developed to reduce individual observer bias and to provide a more consistent method of monitoring temporal changes in the level of sedation. 19 The scale used in the present investigation, to evaluate the depth of sedation, is based on assessment in four separate categories (responsiveness, speech, facial expression and ocular appearance) and has been demonstrated to provide a high discriminatory power of the different levels of sedation.…”
Section: I~oilmentioning
confidence: 99%
“…Previous studies evaluating different techniques of propofol administration during monitored anesthesia care demonstrated that, although the overall quality of sedation, operating conditions and clinical recovery profiles were similar with different administration techniques, the anesthesiologist had to intervene more frequently with the intermittent bolus injection technique than either conventional syringe infusion or target-controlled infusion techniques. 17 While it has been reported in large multicentre trials, that target-controlled infusion systems are easily learned and well accepted by anesthesiologists in their daily practice) 8 A wide variety of objective clinical scoring systems has been developed to reduce individual observer bias and to provide a more consistent method of monitoring temporal changes in the level of sedation. 19 The scale used in the present investigation, to evaluate the depth of sedation, is based on assessment in four separate categories (responsiveness, speech, facial expression and ocular appearance) and has been demonstrated to provide a high discriminatory power of the different levels of sedation.…”
Section: I~oilmentioning
confidence: 99%
“…In Group P, agitation that could have hampered the procedure 15 was not observed at the achieved level of sedation. However, agitation has been reported by Newson et al 16 during mammary biopsy under propofol and local anesthesia.…”
Section: Discussionmentioning
confidence: 94%
“…intermittent boluses, variable rate infusion, target controlled infusion, patient controlled sedation. 6,7 The most commonly used sedation technique is a small dose of midazolam(1-2mg) or propofol (0.5-1 mg/kg) or both followed by a propofol infusion at 25 to 100µg/kg/min. 8 Avramov and White 9 described the combined use of alfentanil (0.3 to 0.4 µg/kg/min) and propofol (25-75 µg/kg/min) infusion for MAC.…”
Section: Discussionmentioning
confidence: 99%